History of an Under-Ice Subsistence Fishery for Arctic Cisco and Least Cisco in the Colville River, Alaska - Moulton, Lawrence L.; Seavey, Brent; Pausanna, Jerry (ARCTIC, 2010)
Arctic cisco (Coregonus autumnalis) and least cisco (C. sardinella) are harvested in the Colville River Delta near Nuiqsut, Alaska, after ice forms in the fall. Arctic cisco targeted by the fall fishery derive from spawning stocks in the Mackenzie River of Canada. Young-of-the-year fish are recruited into the Colville region during August or September, aided by westerly coastal currents generated by predominantly easterly winds. In contrast, anadromous least cisco, harvested as the primary by-catch in the fishery, spawn and winter entirely in the Colville delta and lower river. This study reports on fishery monitoring for the 20-year period 1985 – 2004. During this period, effort in the subsistence fishery showed an increasing trend. Arctic cisco, the target species, averaged over 65% of the annual observed catch, and least cisco averaged 22%. From 1985 to 2002, total harvest of arctic cisco for the combined subsistence and commercial fisheries averaged 38 600 fish (15 958 kg) per year, ranging from a low of 5859 fish (2799 kg) in 2001 to 78 254 fish (31 340 kg) in 1993. During the same period, catches of least cisco averaged 18 600 fish (5819 kg), ranging from a low of 6606 fish (2014 kg) in 2001 to 33 410 fish (11 319 kg) in 1985. The subsistence fishery caught 56% of the total arctic cisco harvest and 42% of the least cisco harvest (in numbers of fish). In the six years for which estimates of both harvest and population level were available, total estimated annual harvest of arctic cisco within the Colville River Delta averaged 8.9% of the available fish, with yearly estimates ranging from 5.4% to 12.9%. For least cisco, the average annual removal rate was 6.8% (range: 2.9% to 13.8%). Le cisco arctique (Coregonus autumnalis) et le cisco sardinelle (C. sardinella) sont pêchés dans le delta de la rivière Colville près de Nuiqsut, en Alaska, après la formation de la glace à l’automne. Les ciscos arctiques qui font l’objet de cette pêche d’automne proviennent de la fraie du fleuve Mackenzie au Canada. Les ...